Early Success With Retention in Care Among People Living With HIV at Decentralized ART Satellite Sites in Yangon, Myanmar, 2015–2016 - Htet, Kyaw Myo; Soe, Kyaw Thu; Oo, Myo Minn; Hone, San; Majumdar, Suman S.; Oo, Htun Nyunt (Frontiers in Public Health, 2019)
Introduction: Myanmar is one of the countries in the Asia-Pacific region hit hardest by the HIV epidemic that is concentrated among urban areas and key populations. In 2014, the National AIDS Programme (NAP) launched a new model of decentralised service delivery with the establishment ART satellite sites with care delivered by HIV peer workers. Methods: ART satellite sites are implemented by non-government organisations to service high burden HIV areas and populations that suffer stigma or find access to public sector services difficult. They provide continuity of HIV care from outreach testing, counselling, linkage to care and retention in care. Anti-retroviral (ART) initiation occurs at health facilities by specialist physicians. We conducted a retrospective cohort study of people living with HIV (PLHIV) who were initiated on ART from 2015-2016 at 5 ART satellite sites in Yangon, Myanmar to assess outcomes and time from enrolment to ART initiation. Results: Of 1,339 PLHIV on ART treatment in 2015-16, 1,157 (89%) were retained, and 5% were lost from care and 5% reported dead, at the end of March 2018. Attrition rates (death and lost-to-follow-up) were found to be significantly associated with a CD4 count ≤ 50 cells/mm3 and having baseline weight ≤50 kg. Median time taken from enrolment to ART initiation was 1.9 months (interquartile range: 1.4-2.5) Conclusion: We report high rates of retention in care of PLHIV in a new model of ART satellite sties in Yangon, Myanmar after three years of follow-up. The delays identified in time taken from enrolment to ART initiation need to be explored further and addressed. This initial study supports continuation of plans to scale-up ART satellite sites in Myanmar. To optimise outcomes for patients and the program and accelerate progress to reduce HIV transmission and end the HIV epidemic, operational research needs to be embedded within the response.